Partnership Cooperation Agreement between Cooperatives and Private Companies to Improve the Economic Competitiveness of the Community in Pasir Jambu, Bandung, West Java - Hamdan Azhar Siregar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The partnership agreement between cooperatives and the private sector in Ciwidey Pasir Jambu, Bandung is very important to improve the competitiveness of cooperatives. In addition, the importance of the agreement is to create certainty of the legal relationship between the parties, therefore the law must be able to encourage the parties to work in order to improve the ability of cooperatives to compete, especially in Pasirjambu. The problems in this study are as follows, how to cooperate in partnership between cooperatives and private companies, what are the obstacles in partnerships between cooperatives and private companies in Pasirjambu. While its use in research is as a contribution to cooperatives and private companies in carrying out development, as well as a contribution to ideas for cooperatives and private companies to look for obstacles in partnerships, while the research method carried out, namely normative jurisprudence, considering that this research is legal research, while data, namely secondary, primary and tertiary data, also field data as support.  In increasing competitiveness in the form of partnerships without definite legal rules, the relationship between the two parties has regressed and uncertain. The implementation of partnerships, based on legal aspects that can provide justice, with the aim of empowering small businesses, cooperatives in national development, namely equal employment and business opportunities, income equality, growing and improving business capabilities, increasing competitiveness, increasing exports, equitable distribution of business ownership and strengthening the structure of the national economy. Through the national business partnership movement, all development actors together renew their determination to mobilize all potentials and strengths to accelerate the growth rate of a just Indonesian nation. Through this movement, the Indonesian nation is prepared to face the challenges and opportunities that open up in free trade